Assessing the legal nature of informed consent and attitude of patients attending outpatient departments of a dental hospital in Bengaluru City: A cross-sectional study - Yashashwini N Simha; N Vanishree; Deepa Bullappa; Keerthi Prasad; L Ramesh (Wolters Kluwer Medknow Publications, 2019)
Background: Informed consent is an ethical and legal requirement for research involving human participants. Aim: This study aimed to assess the patients' awareness of legal nature and attitude regarding the importance of the consent process. Materials and Methods: A descriptive, cross-sectional questionnaire survey was undertaken. Data were collected from the patients who seek care in the Outpatient Department of the Dental College, Bengaluru, for 3 months from June 2014 to August 2014. The data analysis was done using the statistical software SPSS version 14 to generate descriptive statistics. Results: Out of 376 (100%) participants, majority (103 [27.4%]) belonged to the age group of 21-30 years. With regard to the scores, 163 (74.4%) males had a score range of 7-12 as compared to females (117 [74.4%]). Conclusion: Informed consent process is intended to protect patients and to promote an enlightened ethics in patient-dentist relationship. Our study showed that many patients had limited knowledge of the legal implications of signing or not signing consent forms and did not recognize written consent as primarily serving their interest.